Parathyroid Adenoma Presenting as a Brown Tumour of the Mandible. (7th November 2012) - Amin, Kavit; Fu, Bertram; Barbaccia, Carmelo
Abstract : Background . Parathyroid adenoma is the commonest cause of primary hypercalcaemia and usually presents with symptoms/signs of hypercalcaemia. This paper highlights an unusual presentation. Case Report . A 27-year-old female presented with a painful left mandibular swelling, suspicious of neoplasia. A computed tomography (CT) guided biopsy was performed. Based on the histology result, serum calcium was carried out, confirming hypercalcaemia. A left inferior parathyroid adenoma was subsequently removed. CT mandible showed extensive erosive lesions at the left 2nd/3rd inferior molar roots with protrusion to adjacent soft tissues. USS revealed a hypoechoic lesion on the left inferior parathyroid gland. Sestamibi scan showed a focus of MIBI uptake and retention at the inferior aspect of the left thyroid lobe. Conclusion . This case highlights the importance of a thorough history and examination. Clinicians should always bear in mind atypical presentations of parathyroid adenomas, with the need to exclude this differential in the presence of hypercalcaemia.